الأستاذ سعد يبزيان وكتاباته الانثروبولوجيةعن المجتمع العربي المسلم في المهجر - بن ز روال, جمعة (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
This study deals withwriter and journalistProfessor Saadi Bizianwhichisconsidered as a model of Algerian writerswho are interested in anthropologicalwritings about the ArabMuslimcommunity in the Diaspora. Over hiscareerprofessor Saadi wroteseveral books on the Arabcommunity in Europe especially in France, and on Islam and Muslims in the Diaspora, showinghisinterest in severaltopicsincluding social onessuch as marriage and the problem of mixed identity as for Algerian  youngwriters in the Diaspora and the search for cultural identity, and hewroteseveral books about the reality of Islam and Muslims in the West, focusing on their cultural reality in order to preserve the Arab and Islamicidentity.